2016
DOI: 10.1245/s10434-016-5609-1
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutation Status Dictates Optimal Surgical Margin Width in Patients Undergoing Resection of Colorectal Liver Metastases

Abstract: While a 1-4 mm margin clearance in patients with wtKRAS tumors was associated with improved survival, wider resection width did not confer an additional survival benefit. In contrast, margin status-including a 1 cm margin-did not improve survival among patients with mutKRAS tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 34 publications
1
62
0
2
Order By: Relevance
“…As such, it is possible that patients with 4 or more lesions have such aggressive underlying disease biology that technical considerations (use of combined resection and RFA vs. resection alone) have a comparably minor impact on outcomes. Similarly, previous studies from our group and others have shown that the technical adequacy of a resection as measured by the achievement of negative surgical margins has no measurable impact on outcomes among high-risk patients with aggressive disease biology (24,25). However, surgeons should still strive for an R0 resection when technically feasible, as the present study lacks the statistical power to conclusively prove the equivalence of combined resection and RFA vs. hepatic resection alone (26).…”
Section: Discussionmentioning
confidence: 50%
“…As such, it is possible that patients with 4 or more lesions have such aggressive underlying disease biology that technical considerations (use of combined resection and RFA vs. resection alone) have a comparably minor impact on outcomes. Similarly, previous studies from our group and others have shown that the technical adequacy of a resection as measured by the achievement of negative surgical margins has no measurable impact on outcomes among high-risk patients with aggressive disease biology (24,25). However, surgeons should still strive for an R0 resection when technically feasible, as the present study lacks the statistical power to conclusively prove the equivalence of combined resection and RFA vs. hepatic resection alone (26).…”
Section: Discussionmentioning
confidence: 50%
“…The current evidence showed that a margin clearance of 1-4 mm is associated with improved survival compared to R1 only for wild-type KRAS tumors (14). In cases of mutated KRAS tumors were observed no differences between R1 resections or a clearance margin of 1-4, 5-9, or ≥ 10 mm (14). As a strategy for resection, the parenchymal-sparing hepatectomy can be performed safely without compromising oncological outcomes, even for deep-placed or advanced (≥ four lesions with a diameter ≤50 mm) CRLMs (15,16).…”
Section: Discussion Discussionmentioning
confidence: 65%
“…Historically, a 1-cm resection margin was considered associated with better outcomes following CRLMs resection (13). The current evidence showed that a margin clearance of 1-4 mm is associated with improved survival compared to R1 only for wild-type KRAS tumors (14). In cases of mutated KRAS tumors were observed no differences between R1 resections or a clearance margin of 1-4, 5-9, or ≥ 10 mm (14).…”
Section: Discussion Discussionmentioning
confidence: 80%
“…While a 1-4 mm margin clearance in patients with wtKRAS tumors was associated with improved survival, wider resection width did not confer an additional survival benefit. In contrast, margin status, including a 1 cm margin, did not improve survival among patients with mutKRAS tumours (29).…”
Section: R0: Which Resection Margin Width?mentioning
confidence: 71%